Linear (k, n) secret sharing scheme with cheating detection. Issue 13 (20th March 2016) - Liu, Yanxiao
Abstract: Linear ( k, n ) secret sharing scheme with the capability of detecting cheating is considered in this paper. Linear ( k, n ) secret sharing scheme is a class of ( k, n ) secret sharing, where all the n shares of a secret satisfy a linear relationship. It plays an important role in other cryptographic systems, such as multi‐party computation and function sharing schemes. On the other hand, cheating problem in ( k, n ) secret sharing is an important issue, such that cheaters (dishonest players) submit forged shares during secret reconstruction to fool honest players. During decades of research on cheating prevention, vast ( k, n ) secret sharing schemes against cheating have been proposed. However, most of these schemes are not linear schemes because it contains redundant information in their shares to achieve cheating detection. Because linear ( k, n ) secret sharing is an important primitive in threshold cryptography, linear ( k, n ) secret sharing scheme with the capability of cheating detection is also worthwhile to be discussed. In this paper, we propose a linear ( k, n ) secret sharing scheme against cheating based on Shamir's original scheme, which possesses the following merits: (1) Our scheme is just a combination of two Shamir's schemes. Therefore, our scheme can be used in other threshold cryptographic systems, which are based on Shamir's scheme. (2) The size of share in the proposed scheme almost reaches its theoretic lower bound in ( k, n ) secret sharing with cheating detection. (3) In the phase of cheating detection, only one honest player can detect the cheating from other k − 1 cheaters, which achieves a stronger detection effective than the previous linear secret sharing schemes against cheating. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work provides a new secret sharing scheme based on Shamir's landmark work. The new scheme can detect cheating efficiently with linear shares. The ability of cheating detection is much stronger than the previous linear secret sharing schemes.